Sensitization of transient receptor potential vanilloid 4 and increasing its endogenous ligand 5, 6-epoxyeicosatrienoic acid in rats with monoiodoacetate-induced osteoarthritis. Issue 5 (May 2018) - Hinata, Mikie; Imai, Sunao; Sanaki, Takao; Tsuchida, Junji; Yoshioka, Takeshi; Higashino, Kenichi; Yamamoto, Miyuki; Imai, Masayuki; Soga, Masahiko; Horita, Narumi; Fukuda, Isao; Ikeda, Minoru; et al.
Abstract : Abstract: Transient receptor potential vanilloid 4 (TRPV4) receptor modulates pain, and this has been noted in several animal models. However, the involvement of TRPV4 in osteoarthritic (OA) pain remains poorly understood. This study assessed the functional changes in TRPV4 and the expression of its endogenous ligand 5, 6-epoxyeicosatrienoic acid (5, 6-EET) in a rat monoiodoacetate (MIA)-induced OA pain model (MIA rats). Monoiodoacetate-treated rats showed reduced grip strength as compared to sham-treated rats, and this loss in function could be recovered by the intraarticular administration of a TRPV4 antagonist (HC067047 or GSK2193874). By contrast, the intraarticular administration of the TRPV4 agonist, GSK1016790A, increased the pain-related behaviors in MIA rats but not in sham rats. TRPV4 expression was not increased in knee joints of MIA rats; however, the levels of phosphorylated TRPV4 at Ser824 were increased in dorsal root ganglion neurons. In addition, 5, 6-EET was increased in lavage fluids from the knee joints of MIA rats and in meniscectomy-induced OA pain model rats. 5, 6-EET and its metabolite were also detected in synovial fluids from patients with OA. In conclusion, TRPV4 was sensitized in the knee joints of MIA rats through phosphorylation in dorsal root ganglion neurons, along with an increase in the levels of its endogenous ligand 5, 6-EET. The analgesic effects of the TRPV4 antagonist in the OA pain model rats suggest that TRPV4 may be a potent target for OA pain relief. Abstract : Transient receptor potential vanilloid 4 is involved in joint pain in osteoarthritis model rats through its sensitization and increase of its endogenous ligand 5, 6-epoxyeicosatrienoic acid in the knee joint.Supplemental Digital Content is Available in the Text.